Repolarization Precedes Oval Cell–mediated Hepatocytic Regeneration in the CDE Diet Mouse Model. (May 2022) - Zweerink, Susanne; Mueck, Vera; Kraemer, Laurenz P.; Tischler, Eva; Schulte, Sigrid; Goeser, Tobias; Nierhoff, Dirk
The liver has a unique ability to recover from injury unlike any other organ. A poorly understood aspect of liver regeneration is the role of hepatocellular polarization. Neighbor of Punc E11 (Nope) is an oncofetal stem/progenitor cell marker, which is expressed by depolarized adult hepatocytes after cholestatic liver injury and in hepatocellular carcinoma. Liver injury induced by a choline-deficient and ethionine-supplemented diet is reversible if followed by an additional dietary stop interval and enabled us to study the expression of Nope during the induction of chronic liver injury and during subsequent liver regeneration. We could show by quantitative RT-PCR, Western blotting, and immunohistochemistry that the expression of Nope is induced in depolarized adult hepatocytes during injury. However, after another 2 weeks of a normal diet, the polarization of hepatocytes was almost completely restored and the expression of Nope remained limited to bile ducts and oval cells. Using an inducible CK19-lineage tracing model, we could demonstrate that oval cell–mediated hepatocyte regeneration is rare and was preceded by repolarization of hepatocytes. In conclusion, polarization of hepatocytes is an important part of liver regeneration and precedes oval cell–mediated regeneration of the liver. This process can be visualized by a characteristic expression pattern of Nope: